2021
DOI: 10.36233/0507-4088-40
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Epstein–Barr virus (<i>Herpesviridae: Lymphocryptovirus</i>, HHV-4) infection during COVID-19: epidemiological features

Abstract: Introduction. Immunodeficiency underlying the development of severe forms of new coronavirus infection may be the result of mixed infection with SARS-CoV-2 and other pathogens, including Epstein–Barr virus (EBV).The aim is to study the prevalence and epidemiological features of co-infection with SARS-CoV-2 and EBV. Material and methods. A cross-sectional randomized study was conducted in Moscow region from March to May 2020. Two groups were examined for EBV-markers: hospital patients (n = 95) treated for SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 32 publications
0
3
0
6
Order By: Relevance
“…The course of COVID-19 disease may be aggravated in patients that undergo EBV reactivation: these patients had a higher mortality rate and received more immuno-supportive treatment than SARV-CoV-2 patients without EBV coinfection. 28 In fact, Solomay TV et al 29 reported that severe disease and pneumonitis were more common among patients with EBV coinfection. These patients have a more frequent fever, elevated inflammation markers (C-reactive protein), and increased liver enzyme levels.…”
Section: Resultsmentioning
confidence: 99%
“…The course of COVID-19 disease may be aggravated in patients that undergo EBV reactivation: these patients had a higher mortality rate and received more immuno-supportive treatment than SARV-CoV-2 patients without EBV coinfection. 28 In fact, Solomay TV et al 29 reported that severe disease and pneumonitis were more common among patients with EBV coinfection. These patients have a more frequent fever, elevated inflammation markers (C-reactive protein), and increased liver enzyme levels.…”
Section: Resultsmentioning
confidence: 99%
“…Remaining Vδ2 cells displayed markers of activation, suggesting activation and traffic to the lung, similar to what was observed in influenza infection in mice. Again, the reactivation of EBV in severe COVID-19 disease is a factor of morbidity and complications, but the reactivation of other HSVs can also affect the course of disease [35,[264][265][266][267][268]. How this affects γδ T cells and their putative protective or deleterious activity is unknown.…”
Section: Is There a Role For Hhvs In Other Viral Co-infections?mentioning
confidence: 99%
“…1).Wird eine präinfektiöse Dysbiose nachgewiesen, können die entsprechenden Mikrobiomveränderungen durch eine gezielte Darmtherapie behandelt werden.Reaktivierung latenter Viren durch SARS-CoV-2-InfektionAktuelle Studien weisen darauf hin, dass eine Infektion mit SARS-CoV-2 zu einer Reaktivierung latenter Viren führen kann. Dazu gehören v. a. der Epstein-Barr-Virus (EBV) oder humane Herpesviren[19]. Mit dem EBV infizieren sich 90-95 % der Menschen, die meisten davon bereits im Kindesalter.…”
unclassified